Sustaining export potential of spices - Anandaraj, M.; Dinesh, R.; Srinivasan, V. (Indian Horticulture, 2019)
Spices have made impressive strides during the XI plan. During 2011-12, our spices production is about 57.26 lakh tonnes from an area of 30.26 lakh ha. During 2010-11, spices export from India registered an all time high both in terms of quantity and value. In fact, total spices export during 2011-12 indicated an increase of 115% in quantity and 151% in rupee and 141% in dollar terms. Valueadded products also form an integral part of our export basket. Hence, valueaddition/ secondary agriculture would be the major agenda of Indian Council of Agricultural Research (ICAR) and Spices Board. While ICAR is focusing on highvalue compounds from plants, especially spices as a major research platform in the XII plan, the Spices Board hopes that 75-80 per cent of the total export revenue target of $3 billion over the next five years will come from value-addition in mint, chilli, pepper, ginger, turmeric, cumin, garlic, spice oils and oleoresins, nutmeg and cardamom.